Antiinflammatory and anti‐cancer activities of pomegranate and its constituent, ellagic acid: Evidence from cellular, animal, and clinical studies. (7th January 2020) - Baradaran Rahimi, Vafa; Ghadiri, Mobarakeh; Ramezani, Mobina; Askari, Vahid Reza
Abstract : Inflammation is commonly characterized as a defensive and protective reaction of the body to various exogenous or endogenous stimuli, which aims to maintain the body health. Punica granatum (pomegranate) and its constituent ellagic acid (EA) are recently more taken into accounts since their promising pharmacological effects. Therefore, we aimed to obtain a comprehensive review regarding antiinflammatory, anticancer, and antioxidant activities of both pomegranate and EA and their possible involved mechanisms. In the procedure, scientific databases, including Web of Science, PubMed, Scopus, and Google Scholar, were searched in the English language, until the end of January 2019. Pomegranate belonging to the Punicaceae has been used for medical purposes from ancient and in different cultures. Several studies have also supported that EA is the major active compound of pomegranate and possesses antimutagenic, antiinflammatory, antifibrosis, anticancer, and antiaging properties. It has been suggested that pomegranate and EA possess promising immunomodulatory effects in preclinical models as well as human studies through regulation of the T‐cell function and suppressing humoral immunity. Hopefully, we wish that this review and information could be helpful for designing further experiments to investigate the potential protective effects of pomegranate and EA.